PENGARUH SUMBER KARBON DAN AERASI TERHADAP AKTIVITAS DENITRIFIKASI ISOLAT BAKTERI ASLT2 - Lena Novita (Pusbindiklat - LIPI, 2010)
Nitrate is considered as a pollutant in freshwater or estuarine ecosystem which caused eutrofication. Bacteria can be used to reduce nitrate by denitrification process. The aim of this research was to find out the influence of carbon sources and aeration on denitrification of isolated ASLT2 bacteria. The sources of carbon were acetate, succinate, glucose and glycerol under aerob and anaerob conditions. The denitrification process was measuredat seventh day. Isolated ASLT2 bacteria was able to reduce nitrate aerobically and anaerobically in various of carbon sources. The highest activity of aerobic nitrate reduction was found by using acetate as carbon source and anaerobically was found by using succinate as carbon source.